Effects of TolC on the pathogenicity of porcine extraintestinal pathogenic Escherichia coli - Hu, Jin; Wang, Dongfang; Huang, Xingfa; Yang, Yang; Lian, Xin; Wang, Wenjun; Xu, Xiao; Liu, Yulan (Frontiers in Immunology, 2022)
Extraintestinal pathogenic Escherichia coli (ExPEC) is a well-known critical pathogenic zoonosis that causes extraintestinal infections in humans and animals by affecting their immune organs. Recently, research on the outer membrane protein of E. coli, tolerant colicin (TolC), a virulent protein in the formation of the ExPEC efflux pump, has been an attractive subject. However, the pathogenic mechanisms remain unclear. This study aimed to explore the role of TolC in the pathogenesis of the ExPEC strain PPECC42; a complementation strain (Cm-TolC) and an isogenic mutant (ΔTolC) were constructed. Loss of TolC drastically impaired the virulence of ExPEC in an experimental mouse model. ΔTolC showed a substantial decrease in the porcine aortic vascular endothelial cell (PAVEC) adherence, invasion, and pro-inflammatory response, in contrast to that of the wild type, with a reduced survival ratio in both the bacterial load and whole blood in mice. ΔTolC also showed decreased expression of necroptosis signals such as receptor-interacting protein kinase 1, phosphorylated mixed-lineage kinase domain-like protein, and mitochondrial proteins such as phosphoglycerate mutase family member 5. Our data suggest that TolC is closely associated with ExPEC pathogenesis. These results provide scientific grounds for exploring the potential of TolC as an effective drug target for controlling ExPEC infection, screening new inhibitors, and developing new drugs. This will allow for further prevention and control of ExPEC infection.